The evaluation of Regional Medium Term Development Plan Policy of Cianjur regency - Denny Aditya Dwiwarman (Pinisi Business Administration Review, 2021)
Local Government Policies are the main foundation that directs the development process in Cianjur Regency. To achieve the common goal of improving the welfare of the Cianjur community. This policy is expected to be able to respond to changes that occur and provide solutions to any existing problems, because policies that are implemented can be viewed from the effectiveness of the achievements that have been set. Therefore, researchers focused their research on how to evaluate the Cianjur Regency Medium Term Development Plan (RPJMD) Policy in 2011-2016. The research objectives, among others; to describe and analyze the Cianjur Regency Mid-term Regional Development Plan (RPJMD) 2011-2016 Policy Evaluation. The research method uses descriptive, and the research approach uses mixed methods, through a concurrent embedded design model (unbalanced mixture). The results reveal that the success of the RPJMD policy evaluation is empirically determined by the dimensions or aspects of effectiveness, efficiency, adequacy, equity, responsiveness, and dimensions of appropriateness. This study concludes that the evaluation of the Cianjur Regency RPJMD policy in 2011-2016, especially related to the development of road infrastructure based on tourism has not been running optimally, so it has implications for the welfare of the community, especially those in the South Cianjur Region.